A sinister below the skin: A case report on Morel-Lavallée lesion (Indian Journal of Case Reports, 2025)
This case report is to highlight the masquerade presentation of Morel-Lavallée lesions (MLLs) in a young male patient following a road traffic accident. A 38-year-old male, involved in a road traffic accident, was brought to the trauma center in hypotensive shock. Following Advanced Trauma Life Support guidelines, the initial management includes conducting a primary survey to identify any life-threatening injuries and administering intravenous fluids and blood products to stabilize the patient’s hemodynamic status. He has undergone computed tomography scans to confirm the diagnosis of MLLs and evaluate associated injuries. The patient was managed according to the severity of the lesion and associated injuries. MLLs are significant soft-tissue injuries that can occur in the context of high-energy trauma, such as road traffic accidents. This case underscores the necessity of maintaining a high index of suspicion for MLLs in polytrauma patients. Prompt diagnosis using appropriate imaging techniques, coupled with a management flowchart, to prevent complications and optimize patient outcomes.